4(x+2)-5(4x+9)=

Simple and best practice solution for 4(x+2)-5(4x+9)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+2)-5(4x+9)= equation:


Simplifying
4(x + 2) + -5(4x + 9) = 0

Reorder the terms:
4(2 + x) + -5(4x + 9) = 0
(2 * 4 + x * 4) + -5(4x + 9) = 0
(8 + 4x) + -5(4x + 9) = 0

Reorder the terms:
8 + 4x + -5(9 + 4x) = 0
8 + 4x + (9 * -5 + 4x * -5) = 0
8 + 4x + (-45 + -20x) = 0

Reorder the terms:
8 + -45 + 4x + -20x = 0

Combine like terms: 8 + -45 = -37
-37 + 4x + -20x = 0

Combine like terms: 4x + -20x = -16x
-37 + -16x = 0

Solving
-37 + -16x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '37' to each side of the equation.
-37 + 37 + -16x = 0 + 37

Combine like terms: -37 + 37 = 0
0 + -16x = 0 + 37
-16x = 0 + 37

Combine like terms: 0 + 37 = 37
-16x = 37

Divide each side by '-16'.
x = -2.3125

Simplifying
x = -2.3125

See similar equations:

| 0=-9+3n | | 17-15x=-22 | | 7-(m-4)=-3m+2(m+2) | | -2.7(8-x)=13.5 | | x+x+2+x+4=237 | | 75-w=214 | | X^2-90x+950=0 | | 32+(-10)+(-12)-18-(14)= | | 4b-18=2b+6 | | 7p+1=71 | | 4d+9=2d | | 5x-10=3x+12-x | | -(9x-7)+4=6 | | 0.15x+0.07(60000-x)=5000 | | 6(-1+2c)=5(2+2c) | | (9x-7)+4=6 | | 14-18=m | | y=7n-12 | | 4x+2=9x+2 | | 17-9x=18+7x | | 8-9x=18+7x | | -8-9x=18+7x | | 3y-6x=33 | | -235-8m=75 | | 5x+1y=300 | | 0.5(3x+10)(6x)=816 | | 25v+150=225 | | 2.3t=87 | | 3x+8+4x-5= | | x+45=105 | | m+14-18=m | | 5x^2+10x=-4 |

Equations solver categories